SAT0416 ULTRASOUND EVALUATION IN FOLLOW-UP OF URATE-LOWERING THERAPY IN GOUT PHASE 2 (USEFUL-2): DURATION OF FLARE PROPHYLAXIS. (June 2019) - Ebstein, Esther; Forien, Marine; Norkuviene, Eleonora; Richette, Pascal; Mouterde, Gael; Daien, Claire; Ea, Hang Korng; Brière, Claire; Lioté, Frederic; Petraitis, Mykolas; Bardin, Thomas; Ora, Jeremy; et al.
Abstract : Background: Recent studies showed that ultrasonography (US) could be useful for managing urate-lowering therapy (ULT) in gouty patients. In the first phase of the present study (USEFUL-1), we suggested that US was an accurate tool to follow monosodium urate (MSU) crystal dissolution under efficient ULT. For gout flare after starting ULT, prophylaxis is recommended during the first 6 months of ULT. The duration of gout flare prophylaxis over the 6 months is consensual with a grade B recommendation. However, little is known about the probability of relapse according to the urate load modification. Objectives: To determine whether a modification of US features of MSU crystal deposition is associated with reduced number of flares after stopping gout flare prophylaxis. Methods: We performed a 1-year multicentre prospective study including patients with proven gout and US features of gout. The first phase of the study was a 6-month US follow-up after starting (ULT) with gout flare prophylaxis. After 6 months of ULT, gout flare prophylaxis was stopped, followed by a clinical follow-up (month [M] 6 to 12). Outcomes were the proportion of patients with relapse between M6 and M12 according to the modification of US features of gout and determining a threshold decrease in tophus size according to the probability of relapse. Results: We included 79 patients with gout (mean [± SD] age 61.8 ± 14 years, 91% males, disease duration 6.3 ± 6.1 years). Among the 49 completers at M12, 23 (47%) experienced relapse. Decrease in tophus size ≥ 50% at M6 was more frequent without than with relapse (54% vs 26%, P= 0.049). On ROC curve analysis, a threshold decrease of 50.8% in tophus size had the best sensitivity/specificity ratio to predict relapse. Probability of relapse was increased for patients with a decrease in tophus size <50% between baseline and M6 (OR 3.35 [95% confidence interval 0.98; 11.44]). Conclusion: A high reduction in US tophus size is associated with low probability of relapse after stopping gout prophylaxis. US follow-up may be useful for managing ULT and gout flare prophylaxis. Disclosure of Interests: Esther Ebstein: None declared, Marine Forien: None declared, Eleonora Norkuviene: None declared, Pascal Richette Consultant for: Grunenthal, Horizon, Speakers bureau: AstraZeneca, Grunenthal, Gael Mouterde: None declared, Claire Daien: None declared, Hang Korng Ea: None declared, Claire Brière: None declared, Frederic Lioté Grant/research support from: institutional grants from Grunenthal, Ipsen Pharma/Menarini, Novartis, SOBI for the European Crystal Network Workshops, Consultant for: Grunenthal, Novartis, Mykolas Petraitis: None declared, Thomas Bardin Consultant for: Astrazeneca, Grunenthal, Horizon, Novartis, Speakers bureau: Astella, AstraZeneca, Grunenthal., Jeremy Ora: None declared, Philippe Dieudé: None declared, Sebastien Ottaviani: None declared